Texture Evolution of Magnesium Alloy AZ31B Subjected to Severe Plastic Deformation - FRYDRYCH, Karol (Engineering Transactions, 2021)
The paper presents the simulations of texture evolution of the AZ31B Mg alloy subjected to equal channel angular pressing (ECAP) and rotary swaging (RS) processes. It is shown that using the crystal plasticity (CP) parameters obtained by curve fitting conducted on simple mechanical tests with the aid of the evolutionary algorithm, it is possible to correctly predict the texture evolution in both processes. The influence of the initial texture as well as the CP parameters is discussed.